Performance Evaluation of Marshall Mixed Asphalt Concrete-Binder Course (AC-BC) Using Modified LDPE Waste Asphalt with the Wet Method - Efrilia Rahmadona; Kiki Rizky Amalia; Norca Praditya (Jurnal Talenta Sipil, 2026)
The critical issue of Low-Density Polyethylene (LDPE) plastic waste and the need to improve the durability of asphalt pavement underlie this study. Until now, studies on the utilization of plastic waste have focused more on surface layers (AC-WC), while in-depth research on binder layers (AC-BC) is still very limited. The objective of this study is to analyze the effect of LDPE plastic waste utilization on the Marshall characteristics of Asphalt Concrete-Binder Course (AC-BC) mixtures using the wet mix method. This study used an experimental method in the laboratory. After determining the control Optimum Asphalt Content (OAC) of 5.5%, Marshall testing was carried out on AC-BC mixtures with variations in LDPE addition (5%, 6%, and 7%) and variations in asphalt content (5%, 5.5%, 6%, and 6.5%). The results showed that the addition of LDPE increased the Marshall stability value. The highest stability value reached 2402 kg at an LDPE addition rate of 7% with an asphalt content of 5%. In addition, the addition of LDPE also increased the Flow, Marshall Quotient (MQ), Voids in Mix (VIM), Voids Filled with Asphalt (VFA), and Voids in Mineral Aggregate (VMA) values. In conclusion, the utilization of LDPE plastic waste has a significant effect on the mechanical and volumetric characteristics of AC-BC mixtures.